ANALYSIS OF SOCIAL ENGINEERING THREATS IN SOCIAL NETWORKS AND METHODS TO COMBAT THEM. - Ibrayeva Ж.К.; Ibrayev Д.А. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
Observing the growing popularity of social networks as a medium of modern communication, which provides users with extensive opportunities for information exchange, there is an unseen rise in the threats of spreading malicious information associated with the use of social engineering methods. This study focuses on the phenomenon of social engineering aimed at manipulating social network users to extract confidential data, damage reputations, spread disinformation, or cause other harm. The relevant key mechanisms of social engineering, the reasons for users’ vulnerability to such attacks, and the potential consequences for information security are considered. The work also offers recommendations for countering these threats, including enhancing digital literacy, developing protective technologies, and improving regulatory mechanisms. This research is relevant to specialists in the field of information security, social sciences, and anyone interested in protecting the digital environment from manipulation and malicious information.